Relationship Between GDP And GDS In The UAE: ARDL Bound Testing Approach - Hussain, Majeed Ali; J. Saaed, Afaf Abdull (Archives of Business Research, 2018)
This study explores the relationship between Gross Domestic Product (GDP) and Gross Domestic Saving (GDS) in United Arab Emirates (AUE covering the period 1980 – 2013, using the autoregressive distribution lag (ARDL) cointegration framework. Granger Causality test were employed in the empirical analysis. Using Augmented Dickey-Fuller (ADF) and Phillip-Perron (PP) stationarity test, the variable proved to be integrated of the order one 1(1) at first difference. The results based on the bounds testing procedure confirm that a long-run relationship between GDP and GDS exist. The results indicate that domestic savings is significantly positively related to growth in UAE These results are consistent with the findings of Mphuka (2010), Abu (2010), Nurudeen (2010) and Mohan (2006). The econometric evidence that LGDS causes LGDP and there is evidence that saving is the driver of economic growth in UAE. Considering the findings mentioned above, we make the following recommendations; Measures to increase growth and economic diversification in UAE should aim to promotes domestic savings and increases domestic savings overall. Fiscal and Monetary policies that allow for increased savings and that enhances domestic savings is vital. The study recommends the need for development of financial instruments to encourage domestic savings.